GAYA KEPEMIMPINAN KYAI DI PONDOK PESANTREN AL-QUR’AN AL-FALAH 2 NAGREG - Hasyudi, Ismi; Eep Saepuloh; Rismawati; M. Tajudin Zuhri; Nenden Munawaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the leadership style of KH. Cecep Abdullah Syahid at Pondok Pesantren Al-Qur’an Al-falah 2 Nagreg, which integrates Islamic principles with a paternalistic and transformative approach. The research aims to analyze the role of Kyai's leadership in fostering pesantren culture, enhancing student discipline, and maintaining pesantren relevance in the modern era. This qualitative study employs in-depth interviews, observations, and documentation.The findings reveal that the Kyai's exemplary behavior serves as a foundation for effective leadership, building strong emotional connections with students. Decision-making based on syura fosters collective responsibility, while the pesantren's culture reflects Islamic values such as discipline, cooperation, and dedication. Additionally, the Kyai successfully addresses modernization challenges by integrating technology into the learning process without compromising traditional values.This study concludes that KH. Cecep Abdullah Syahid's leadership style not only creates an ideal Islamic educational environment but is also relevant for other Islamic educational institutions in navigating the challenges of the modern era.